Experiences of nursing students regarding clinical placement and support in primary healthcare clinics: Strengthening resilience - Beauty M. Zulu; Emmerentia du Plessis; Magdalena P. Koen (AOSIS, 2021)
Background: This research addressed the need to have a deeper understanding of nursing students' experiences of clinical placement and support in primary healthcare (PHC) settings. Aim: To explore and describe the experiences of nursing students' clinical placement in PHC settings. Setting: The study was conducted at PHC clinics in a specific province in South Africa. Method: A qualitative, exploratory, descriptive and contextual research design was used. The population comprised fourth-year nursing students selected using purposive sampling. Five semi-structured focus group interviews were conducted. Data saturation determined the sample size which comprised 25 nursing students. Thematic data analysis produced four main themes. Results: The main themes were (1) the meaning of placement, (2) experiences of clinical placement, (3) needs for support, and (4) resilience of nursing students. Conclusions: Nursing students encountered negative and positive experiences. Both experiences confirmed that PHC settings can be valuable learning opportunities for nursing students. Nursing students appreciated the supervision of professional nurses who created an atmosphere conducive for teaching and learning by welcoming and encouraging nursing students' independence. Recommendations include: appointing a professional nurse specifically for supervision of nursing students, tutor support before summative examinations, improvement of services, including the availability of resources. Contribution: This article contributes to awareness of how nursing students manage to stay resilient irrespective of negative experiences during clinical placement and how tutors and professional nurses can support them. The study's recommendations can guide professional nurses, nurse educators, nurse managers and other healthcare PHC workers to support nursing students.